Exodus Event: Its Historical Kernel. AStudy of the Origin of the Biblical People and the Egyptian Exodus - Gurukkal, Rajan (Asian Horizons, 2007)
George Edayadiyil, CMI, Exodus Event: Its Historical Kernel. A Study of the Origin of the Biblical People and the Egyptian Exodus. Vol. 1. From Exodus and Beyond. Bangalore: ATC, 2007, pages xvii + 156.ISBN81-7086-429-1.